Etiologic analysis of 100 anatomically failed dacryocystorhinostomies - Dave TV (Dove Medical Press, 2016)
Tarjani Vivek Dave, Faraz Ali Mohammed, Mohammad Javed Ali, Milind N Naik The Institute of Dacryology, L V Prasad Eye Institute, Hyderabad, India Background: The aim of this study was to assess the etiological factors contributing to the failure of a dacryocystorhinostomy (DCR). Patients and methods: Retrospective review was performed in 100 consecutive patients who were diagnosed with anatomically failed DCR at presentation to a tertiary care hospital over a 5-year period from 2010 to 2015. Patient records were reviewed for demographic data, type of past surgery, preoperative endoscopic findings, previous use of adjuvants such as intubation and mitomycin C, and intraoperative notes during the re-revision. The potential etiological factors for failure were noted. Results: Of the 100 patients with failed DCRs, the primary surgery was an external DCR in 73 and endoscopic DCR in 27 patients. Six patients in each group had multiple revisions. The mean ages at presentation in the external and endoscopic groups were 39.41 years and 37.19 years, respectively. All patients presented with epiphora. The most common causes of failure were inadequate osteotomy (69.8% in the external group and 85.1% in the endoscopic group, P=0.19) followed by inadequate or inappropriate sac marsupialization (60.2% in the external group and 77.7% in the endoscopic group, P=0.16) and cicatricial closure of the ostium (50.6% in the external group and 55.5% in the endoscopic group, P=0.83). The least common causes such as ostium granulomas and paradoxical middle turbinate (1.37%, n=1) were noted in the external group only. Conclusion: Inadequate osteotomy, incomplete sac marsupialization, and cicatricial closure of the ostium were the most common causes of failure and did not significantly differ in the external and endoscopic groups. Meticulous evaluation to identify causative factors for failure and addressing them are crucial for subsequent successful outcomes. Keywords: failed DCR, etiologies, cicatricial closure, osteotomy, endoscopy